Clinical Presentations and Genetic Characteristics of Late-Onset MADD Due to ETFDH Mutations in Five Patients: A Case Series - Tang, Zhenchu; Gao, Shan; He, Miao; Chen, Qihua; Fang, Jia; Luo, Yingying; Yan, Weiqian; Shi, Xiaoliu; Huang, Hui; Tang, Jianguang (Frontiers in Neurology, 2021)
Background: Late-onset multiple acyl-CoA dehydrogenase deficiency (LO-MADD) describes a curable autosomal recessive genetic disease caused by ETFDH mutations that result in defects in ETF-ubiquinone oxidoreductase. Almost all patients are responsive to riboflavin. This study describes the clinical presentations and genetic characteristics of five LO-MADD patients. Methods: From 2018 to 2021, we collected clinical and genetic data on five patients diagnosed with LO-MADD at our hospital and retrospectively analyzed their clinical characteristics, laboratory examination, electromyography, muscle biopsy, genetic analysis, and outcome data. Results: This study included three males and two females, with mean onset age of 37.8 years. Fluctuating exercise intolerance was the most common presentation. Serum creatine kinase (CK) levels were significantly elevated in all patients, and plasma acylcarnitine profiles revealed an increase in long-chain acylcarnitine species in three cases. The urinary organic acid study revealed a high level of hydroxyglutaric acid in all patients. Electrophysiology demonstrated myogenic impairment. Muscle biopsies revealed lipid storage myopathy. Molecular analysis identified nine mutations (three novel and six reported) in ETFDH. Exercise intolerance and muscle weakness were dramatically improved in all patients treated with riboflavin (100mg) daily following diagnosis. Conclusions: LO-MADD is caused by ETFDH variants and responds well to riboflavin. Three novel ETFDH pathogenic variants were identified, expanding their spectrum in the Chinese population and facilitating future interpretation and analysis of ETFDH mutations.